2012
DOI: 10.3727/096368912x638847
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Reperfused Ischemia with Adipose-Derived Stem Cells in a Preclinical Swine Model of Myocardial Infarction

Abstract: The aim of the study was to determine the long-term effect of transplantation of adipose-derived stromal cells (ADSCs) in a preclinical model of ischemia/reperfusion (I/R). I/R was induced in 28 Goettingen minipigs by 120 min of coronary artery occlusion followed by reperfusion. Nine days later, surviving animals were allocated to receive transendocardial injection of a mean of 213.6 ± 41.78 million green fluorescent protein (GFP)-expressing ADSCs (n = 7) or culture medium as control (n = 9). Heart function, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 34 publications
2
62
0
1
Order By: Relevance
“…Amelioration of IR damage has been described previously using MSCs, cardiac stem cells and induced pluripotent stem cells [307][308][309][310]. Transendocardial injections of ASCs in a minipig model of IR injury results in long-lasting improvements in cardiac function, along with increased angiogenesis and vasculogenesis [311]. Higher numbers of CD31+ve and vWF+ve cells have also been found in models of lung IR following ASC injection, suggesting increased vessel formation [312].…”
Section: Asc-directed Tissue Regeneration: the Role Of Vascularizationmentioning
confidence: 96%
“…Amelioration of IR damage has been described previously using MSCs, cardiac stem cells and induced pluripotent stem cells [307][308][309][310]. Transendocardial injections of ASCs in a minipig model of IR injury results in long-lasting improvements in cardiac function, along with increased angiogenesis and vasculogenesis [311]. Higher numbers of CD31+ve and vWF+ve cells have also been found in models of lung IR following ASC injection, suggesting increased vessel formation [312].…”
Section: Asc-directed Tissue Regeneration: the Role Of Vascularizationmentioning
confidence: 96%
“…To date, ADSCs have become excellent candidates for research and clinical applications. Many studies have shown that ADSC transplantation efficiently improved almost all symptoms of certain diseases, such as liver fibrosis (Harn et al, 2012), nerve defects (Gu et al, 2012;Liu et al, 2011;Santiago et al, 2009), ischemia (Mazo et al, 2012;Rigol et al, 2010), skeletal muscle injury (Pecanha et al, 2012), passive chronic immune thrombocytopenia (Xiao et al, 2012), and myocardial infarction (Yang et al, 2012) in animals, and systemic sclerosis in humans (Riordan et al, 2009;Scuderi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19] We and others have shown that isolated ASC phenotypically and functionally overlap substantially with pericytes and SMC. networks.…”
Section: Editorial See P 752 In This Issue See P 751mentioning
confidence: 99%